Critical thinking: a transformative component in teacher training (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2019)
Critical thinking in teaching has shown weaknesses in the application of strategies that lead to its development due to a lack of knowledge among educators, where the objective is to describe teacher training from a critical thinking perspective as a transformative vision, whose precepts are based on Montero (2001); Kincheloe (2001), who note that it is important to carry out activities to teach thinking for critical and comprehensive action. Using a quantitative approach, case study, survey, and questionnaire as data collection methods. As a result, teaching practice is limited to traditional workshops, and tools for proper argumentation are rarely applied to value judgments.